A review of dual-spin projectile stability - Norris, James; Hameed, Amer; Economou, John; Parker, Simon (Defence technology, 2020)
This paper gives a succinct review of dual-spinprojectile stability and some technologies relating to them. It describes how the traditional stability factors from linear projectile theory are modified to better describe a controlled dual-spin projectile. Finally, it reviews works which have investigated how different aspects of a controlled dual-spin design can affect flight stability, primarily airframe structure and canard properties. A conclusion is given, highlighting important guidelines from the enclosed discussions.